PENGUATAN KOMPETENSI MAHASISWA SEBAGAI CALON PENDIDIK AGAMA HINDU YANG BERKARAKTER - I Wayan Agus Gunada; I Wayan Suastra (Institut Agama Hindu Negeri Gde Pudja Mataram, 2023)
This study aims to describe and explain the importance of increasing understanding of the competencies that a prospective educator must possess. Today educators have a fairly central role in teaching and educating to transform theory into practical skills for students. The role of the educator, who should be an example for students, in some cases, becomes a criminal, one of which is a case of harassment of students. So building character is not only an obligation of a student but also for a student's perspective educator himself, let alone a prospective religious educator. This research is centred on a literature review with an analysis of relevant libraries. Based on the analysis of the relevant libraries, the results are obtained, namely based on existing regulations. To become an educator, you must have qualifications, competencies and certifications. The competencies that must be possessed are professional, pedagogic, social and personal competencies. Besides, prospective educators must have an understanding of the importance of literacy. Character is also an integral part of forming prospective religious educators to become educators who can be an example for their students. The results of this study can strengthen insights and information for prospective educators and become a literature review for relevant research in the future.